THE PROBLEMS OF LAND REFORM INCOMPLETENESS IN UKRAINE - Myroslav BOHIRA; Nazar STUPEN; Ruslana TARATULA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The course of Land reform in Ukraine is analyzed, its positive and negative results are revealed both in the issues of rational agricultural lands use, especially in solving the ecological component in land use and in the problems of social and economic development of rural territories. Legislative documents and subordinate acts of the Ukrainian state that regulate carrying out Land reform or have a direct relation to Land reform and other scholars’ research on this topic is the main database for conducting scientific studies. According to the authors, the conducted studies show that in the theoretical positions of Land reform all the problematic issues concerning the land use organization; mainly environmental components have not been taken into account. Moreover, the issues of the development of village infrastructure and raising the peasants’- landowners’ living standards have not been also taken into consideration. Generally, the goal of Land reform in Ukraine has not been achieved to the full extent. It has led to significant shortcomings in agricultural production and a decrease of Ukrainian peasants’ living standards. The scientific novelty of the article is the issue that it is indispensable to hold a national discussion of the theoretical foundations of the reform before carrying out the reform in the state, which affects more than half the population. The scientific approaches for state structures regarding correction of drawbacks in land use, which have been revealed in the course of carrying out Land reform, are developed and recommended and ways of solving some problems of rural territories development are suggested.